Enteroparasitism and Risk Factors Associated with Clinical Manifestations in Children and Adults of Jalisco State in Western Mexico - María de la Luz Galván-Ramírez; Ana Luisa Madriz-Elisondo; Cynthia Guadalupe Temores Ramírez; Jorge de Jesús Romero Rameño; Dania Araceli de la O Carrasco; Marco Antonio Cardona López (Osong Public Health and Research Perspectives, 2019)
Objectives To determine the prevalence and risk factors associated with intestinal parasites in the population of San Juan Cosala, Jalisco, Mexico. Methods A total of 277 samples from 104 participants were analysed using direct smear, flotation, formaldehyde/ethyl acetate, and modified Kinyoun’s acid-fast stain methods. The Graham method was applied only for samples from children under 12 years of age for the diagnosis of Enterobius vermicularis. Results The prevalence of parasite infections in the study population was 77.9% including: Entamoeba histolytica/E. dispar/E. moshkovskii/E. bangladeshi (37.5%), Giardia intestinalis (11.5%); commensals: Endolimax nana (44.2%), Entamoeba coli (27.9%), Chilomastix mesnili (6.7%) and Iodamoeba bütschlii, (2.9%); emerging intestinal protozoans: Blastocystis spp. (49%), Cryptosporidium spp. (7.7%) and Cyclospora cayetanensis (2.9%); and helminths: Enterobius vermicularis (18.3%) and Ascaris lumbricoides (5.8%). The results also showed that 58.64% of the studied population presented polyparasitism. A significant association was found between protozoan infections and housewives, and houses that were not built with concrete ceilings, brick walls and cement floors (p < 0.05). Conclusion Polyparasitism was observed in over half the study population. The most prevalent parasite was Blastocystis spp, whilst the prevalence of helminths was less than that of protozoans. The risk factors for infection to intestinal parasites were being a housewife and not having solid brick, cement and concrete materials for house construction.